Determinants of the Price and Non-price Terms of Bank Loans: A Study of Malaysian SMEs - Shaista Wasiuzzaman (Australasian Accounting, Business and Finance Journal, 2021)
The aim of this study is to investigate the determinants of the price and non-price terms of banks loans to SMEs. Responses from a survey questionnaire answered by 74 SMEs that had applied for and were granted bank loans is analyzed using SEM-PLS. The results indicate that the condition and capacity of the SME is significant in influencing interest rates while the SME’s ability to provide collateral, its capital and the character significantly influence the non-price terms. Soft information is highly significant in influencing both the price and non-price terms.
Keywords: Bank Lending; Loan pricing; Loan terms and conditions; SMEs